Effects of growth control on yield and fruit quality of the apple cultivar ‘Rubin’ - Kviklys, Darius; Viskelis, Jonas; Lanauskas, Juozas; Uselis, Nobertas; Liaudanskas, Mindaugas; Janulis, Valdimaras (Agricultural and Food Science, 2020)
The effect of tree growth-control technologies on apple tree vegetative development, productivity and fruit quality was investigated with apple cultivar ‘Rubin’ on dwarf rootstock P 60 at the Institute of Horticulture, Lithuanian Research Centre for Agriculture and Forestry in 2015–2018. Eight treatments were established combining tree trunk incision by chainsaw before flowering, application of prohexadione-calcium in different dose and time, summer pruning in August and root pruning before flowering. Root pruning from both sides of the tree significantly reduced tree trunk diameter, shoot length and pruning weights but at the same time reduced fruit weight. It increased tree productivity and enhanced fruit colouring. Two applications of prohexadione-calcium significantly reduced mean shoot length and increased average fruit weight. Summer pruning had a positive impact on fruit colouring. Trunk incisions enhanced leaf P, K and Fe content. Pro-Ca increased leaf Ca content. Trees root pruned from both sides had one of the lowest contents of all tested minerals. All tree growth-control technologies had a positive impact on tree productivity , fruit quality and bearing stability comparing with control treatment.